2008
DOI: 10.1152/ajprenal.00137.2008
|View full text |Cite
|
Sign up to set email alerts
|

Enhanced amiloride-sensitive superoxide production in renal medullary thick ascending limb of Dahl salt-sensitive rats

Abstract: The aims of the present study were to determine whether superoxide (O(2)(-)) production is enhanced in medullary thick ascending limb (mTAL) of Dahl salt-sensitive (SS) rats compared with a salt-resistant consomic control strain (SS.13(BN)) and to elucidate the cellular pathways responsible for augmented O(2)(-) production. Studies were carried out in 7- to 10-wk-old male SS and SS.13(BN) rats fed either a 0.4% NaCl diet or a 4.0% NaCl diet for 3 days before tissue harvest. Tissue strips containing mTAL were i… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

4
23
1

Year Published

2009
2009
2019
2019

Publication Types

Select...
8

Relationship

5
3

Authors

Journals

citations
Cited by 17 publications
(28 citation statements)
references
References 26 publications
4
23
1
Order By: Relevance
“…Recent studies have clarified one of these pathways, which involves H ϩ transport in the mTAL that when activated stimulates a Nox-mediated production of O 2 ·Ϫ independently of active Na ϩ transport (85,139). By utilizing SS HV1…”
Section: Consequences Of Increased Mtal Luminal Flow and Namentioning
confidence: 99%
See 1 more Smart Citation
“…Recent studies have clarified one of these pathways, which involves H ϩ transport in the mTAL that when activated stimulates a Nox-mediated production of O 2 ·Ϫ independently of active Na ϩ transport (85,139). By utilizing SS HV1…”
Section: Consequences Of Increased Mtal Luminal Flow and Namentioning
confidence: 99%
“…It is the imbalance between both reduced NO and elevated O 2 ·Ϫ (and H 2 O 2 ) production in SS rats that appears to tilt the balance toward a state of oxidative stress even before a switch to a high-salt diet, which accelerates this process and leads to the rapid rise in arterial pressure and renal injury (32,130,133,139).…”
Section: Medullary O 2 ·ϫ No and H 2 O 2 As Determinants Of Blood mentioning
confidence: 99%
“…Both NOX2 and NOX4 have been detected in mTAL, and further studies will be required to determine which of these isoforms are activated by H ϩ efflux. Importantly, O 2 Ϫ production observed in response to a number of stimuli, as well as basal ROS levels in the outer medulla, are sensitive to dimethyl amiloride, indicating that this pathway is likely an important source of ROS in vivo (22,31,32). Further, the activity of these H ϩ currents has been found to be greater in mTAL from Dahl salt-sensitive rats compared with a saltresistant control strains, indicating a potential role of this transporter toward the development of oxidative stress in the kidney and salt-sensitive hypertension (31).…”
Section: Tubular H ϩ Efflux and O 2 ϫ Productionmentioning
confidence: 99%
“…Importantly, we found that the rate of O 2 ·Ϫ production in SS mTAL was greater than that of SS. 13 BN in response to increments in extracellular NaCl concentration (59). Furthermore, this difference was enhanced in mTAL taken from rats 3 days after the advent of high-salt feeding (59).…”
Section: Searching For the Source Of Augmented O 2 ·ϫ In The Kidney Omentioning
confidence: 99%
“…To determine whether NADPH oxidase-dependent O 2 ·Ϫ production was elevated in medullary thick ascending limb (mTAL) tubular segments from Dahl SS, we utilized live-cell imaging of microdissected nephron segments loaded with the free radical indicator dihydroethidium (DHE) and compared the relative rates of O 2 ·Ϫ production between mTAL from SS and SS.13 BN rats (59). Given our hypothesis that "elevated O 2 ·Ϫ production resulted from increased Na ϩ delivery and tubular work following initiation of high-salt feeding," the most physiologically relevant stimuli would have been to perfuse isolated nephron segments at various flow rates to mimic alterations in Na ϩ intake and luminal NaCl delivery.…”
Section: Searching For the Source Of Augmented O 2 ·ϫ In The Kidney Omentioning
confidence: 99%